PARTISIPASI MASYARAKAT DALAM PENGEMBANGAN PARIWISATA OKSIGEN GILI IYANG KABUPATEN SUMENEP - Melyana Ulfa; Mochamad Erik Ibrahim; Kendry Widiyanto; Yusuf Hariyoko (PRAJA observer: Jurnal Penelitian Administrasi Publik (e- ISSN: 2797-0469))
Gili Iyang Island is one of the most beautiful islands known for its very high oxygen content to attract both local and foreign tourists to visit the island of Gili Iyang. There are several reasons that are the most important factors in the development of tourism, including its remote location making transportation facilities, some facilities for tourists are inadequate, many people in the Gili Iyang area are unable to speak Indonesian. From this explanation, the author uses a qualitative approach in the form of descriptive research.